Analisis Usaha Industri Rumahan Emping Melinjo Di Desa Cilowong Dengan Menggunakan Pendekatan Rasio Dan Profitabilitas - Lorhenson Debataraja (BISMA (Bisnis dan Manajemen), 2017)
The purpose of this research is to know the amount of cost, acceptance, profit, profitability, and business risk emping melinjo household scale in Cilowong Village, Taktakan sub-district, Serang city, Banten. Determination of sample area is done by purposive that is Kampung Cilowong. Sampling of respondents is done by proportional. Its population is all businessmen emping melinjo household scale in Cilowong Village. The number of respondents as many as 40 people. The data used are primary data and secondary data. Technique of collecting data is done by observation, interview, and recording. Data analysis using ratio and profitability approach. Based on the results of the study it can be concluded that: 1) Average total cost incurred of Rp40.085.250,00; 2) emping melinjo which sold an average of 8,100Kg with price per Kg Rp 20.000,00. The amount of gross receipts is Rp51.300.000,00. The profit earned an average of Rp11,214,750.00 with an average of 9 employees; 3) Profitability of 21.86%; and 4) industrial efficiency of 0.27.